Bio-based, biodegradable and amorphous polyurethanes with shape memory behavior at body temperature. Issue 23 (29th April 2019) - Dou, Hui-Min; Ding, Ji-Heng; Chen, Hao; Wang, Zhen; Zhang, A.-Fang; Yu, Hai-Bin
Abstract : A series of bio-based, biodegradable and amorphous polyurethanes with shape memory behavior at body temperature were synthesized. Abstract : In this work, a series of bio-based, biodegradable and amorphous shape memory polyurethanes were synthesized by a two-step pre-polymerization process from polylactide (PLA) diol, polycaprolactone (PCL) diol and diphenylmethane diisocyanate-50 (MDI-50). The ratio of PLA diol to PCL diol was adjusted to investigate their thermal and mechanical properties. These bio-based shape memory polyurethanes (bio-PUs) showed a glass transition temperature ( T g ) value in the range of −10.7–32.5 °C, which can be adjusted to be close to body temperature. The tensile strength and elongation of the bio-PUs could be tuned in the range from 1.7 MPa to 12.9 MPa and from 767.5% to 1345.7%, respectively. Through a series of shape memory tests, these bio-PUs exhibited good shape memory behavior at body temperature. Among them, PU with 2 : 1 as the PLA/PCL ratio showed the best shape recovery behavior with a shape recovery rate higher than 98% and could fully reach the original shape state in 15 s at 37 °C. Therefore, these shape memory bio-PUs are promising for applications in smart biomedical devices.